ANALISIS HUKUM ISLAM TENTANG PENETAPAN HAK WASIAT WAJIBAH TERHADAP AHLI WARIS NON MUSLIM (STUDI PUTUSAN NO. 0141/PDT.P/2012/PA. SBY) - FEBRI SILVIA DEWI (PREMISE LAW JURNAL, 2015)
Inheritance occurs when there is a death (of the testator). This principle is clarified in Article 830 of the Civil Code (Burgerlijke Wetboek). The distribution of inheritance is done with two ways: voluntarily and involuntarily. Voluntary way ends in reconciliation and coercion by judge’s verdict. The research used descriptive analytic and judicial normative method. The distribution of inheritance through Reconciliation Deed depends on agreement of the conflicting parties. If the inheritance is tangible, the delivery must be tangibles; but, if the inheritance is assessed value, the implementation should be through the selling of the inheritance and the proceeds of the sale are distributed according to the initial agreement. The settling for direct distribution of tangibles and assessed value should be done through the process done by heirs; they should get the Inheritance Rights, Partition, and Distribution Letters. The settlement for dispute in inheritance should not always through litigation; it can be through reconciliation which is more favorable. It is better to make authentic Deed in performing the reconciliation so that there will be legal force. Keywords: Inheritance Distribution, Reconciliation Deed, Legal Force